A COMPARISON OF CHILD PROTECTION LAW BETWEEN INDONESIA AND MALAYSIA - Jauhari, Iman (UI Scholars Hub, 2014)
This paper aims to compare child protection law between Indonesia and Malaysia especially in terms of family law (marriage), child definition and age limit, as well as other foundational principles. Content analysis method of a variety of relevant references is used and a comparative approach to child protection law in Indonesia and Malaysia is taken. There are many similarities between child protection law in Malaysia and Indonesia, in which both systems specify the state, family, and parents responsibilities towards children. Also specified are handling of child’s position, guardianship, rearing, adoption, religion, and abandonment. In addition, special protection such as maintenance, recovery, custody, care, investigation, nursing, education, prevention of economic exploitation, prevention of sexual abuse, prevention of child torture, and disability treatment are also included. This paper concludes that in Malaysia child protection law has been fully synthesised in Children Act of 2001 (Act 611), while in Indonesia child protection law is scattered in a number of laws related to children including the Child Protection Law.